Análise da concentração de fluoretos em dentifrícios clareadores e dessensibilizantes - Oliveira, Marcelo Bruno Lemos de (2023)
Fluoride dentifrices are the formulations for personal use most used for oral care, however, to be effective there is a need for a minimum concentration of fluoride and that it be in a soluble form, a fact that Brazilian legislation and other countries do not require from manufacturers. In response to consumers' new aesthetic and therapeutic demands, new formulations are constantly emerging, an example being toothpastes with whitening effects and formulations composed of substances for an antisensitivity effect. Despite the increase in studies evaluating the concentration of soluble fluoride, there are no specific studies on these formulations. A total of 39 commercial products from different lots (n=3) were analyzed using ion-electrode-selective, in order to verify the concentration (μg/g or ppm F-) of total fluoride (TF), total soluble fluoride (TSF) and ionic fluoride (IF). For comparative data analysis, ANOVA was applied followed by Tukey's test for multiple comparisons. The confidence level adopted was 95%. Of the 39 evaluated dentifrices, 43.6% contained sodium fluoride (NaF) and 56.4% sodium monofluordosphate (MFP), all these types of fluoride being incorporated into the dentifrice formulation. The concentration (mean ± SD; n=39) of TF found in the dentifrices was 1159.0 ± 177.1. The F concentration in the TSF fraction was 950.2 ± 164.9. The IF results were 621.3 ± 329.9. When the measured TF was compared with the TSF, the active fraction, 100% of the dentifrices showed TSF lower concentration than the TF, being 64.1% with soluble concentrations below 1000 ppm F. Statistically significant differences were found in the concentrations of the dentifrices when compared measured total fluoride (TF) and total soluble fluoride (TSF), as well as between declared and measured total fluoride (TF) concentrations, within each product. The samples worked in the present study showed, for the most toothpastes, diverget values with what was declared by the manufacturers. Furthermore, all samples showed soluble concentrations lower than total concentrations.